EFEKTIVITAS PROMOSI KESEHATAN MPASI BERBAHAN PROTEIN HEWANI TERHADAP STATUS GIZI BAYI USIA 6-12 BULAN - Yusika, Kiki; Tristianur, Sinta (Journal of Midwifery Tiara Bunda, 2025)
Providing correct complementary feeding (MPASI) will greatly influence the child’s growth, development process and intelligence. Inappropriate complementary feeding will cause problems in the nutritional status of children, which are undernutrition and malnutrition. Based on the results of the 2022 Indonesian nutritional status survey, Tangerang City has a stunting rate of 11,8%. Objective : This study aims to determine the effectiveness of health promotion about MPASI made from animal protein on the nutritional status of infants 6-12 months. Methodology : This study used a pre-experimental design one group pretest-posttest approach. Samples were collected using total sampling totaling 30 infants 6-12 months in the work area of the Midwife Independent Practice ST Tangerang City. The questionnaire has been tested for validity and reliability. Data analysis was performed using the Wilcoxon Signed Rank Test. Results : Prior to health promotion, 7 (23,3%) of the 30 infants 6-12 months are undernutrition. After being given MPASI made from animal protein health education, 30 infants (100%) have normal nutritional status. The Wilcoxon test shows p value = 0.008 which means that there was a significant effect of health education on the nutritional status of infants 6-12 months.